Determinants of E-Learning Acceptance Among Intel's Employees - Chye, Mui Sung (2011)
This study examines factors that influence e-learning acceptance among Intel's users. The study was a cross sectional study where respondents' perception was measured at one point in time. 97 respondents participated in this study. In this study, three factors were tested to understand the level of acceptance among e-learning users. Correlation analyses were conducted to test the relationship between individual factors, system factors and organizational factors and e-learning acceptance, whereas descriptive analysis was conducted to analyze demographic characteristics of participants. To test which factor has the significant contribution towards e-learning acceptance, regression analysis was conducted. The results show that there was an association between all the three factors (individual, system and organizational) and e-learning acceptance. The findings indicated that all these three factors are important that can influence users' acceptance towards e-learning system. Though all the three factors indicate significant positive relationship with e-learning acceptance, system factor made the strongest contribution to the e-learning acceptance.